Determination of views about usage level of education technologies of teachers at electronic and computer department of technical high school - (:unkn) unknown (DRUNPP-SARAJEVO, 2011)
This study is explored views about usage level of education technologies of teachers at electronic and computer department of technical high school. In this descriptive study, data are collected using Egitim Yoneticileri ve Ogretmenleri bilim teknolojilerinin ve bilesim teknolojilerinden. yararlanmalarini engelleyen nedenler scale that is developed by Mehmet Durdu Karsli et al. (2002). Research universe is teachers at Electronic and Computer Departments at 2009-2010 education semester. Research sample is 39 teachers at 6 schools that are selected according to simple casual sampling method in Istanbul, Turkey. Frequency, percentage, t test, Krukal Wallis and Anova statistical method are used for data analysis. Difference between being able to technology use levels of teachers at Electronic Computer Department who participated to the research are seen according to variables such as sexuality, revenue of family, department, duty duration. However views about ability of being able to technology use are offered.
Keywords: Education Technology; Attitude about Education Technology Usage